Ca2+-Sensor Neurocalcin δ and Hormone ANF Modulate ANF-RGC Activity by Diverse Pathways: Role of the Signaling Helix Domain - Duda, Teresa; Pertzev, Alexandre; Ravichandran, Sarangan; Sharma, Rameshwar K. (Frontiers in Molecular Neuroscience, 2018)
Prototype member of the membrane guanylate cyclase family, ANF-RGC (Atrial Natriuretic Factor Receptor Guanylate Cyclase), is the physiological signal transducer of two most hypotensive hormones ANF and BNP, and of the intracellular free Ca2+. Both the hormonal and the Ca2+-modulated signals operate through a common second messenger, cyclic GMP; yet, their operational modes are divergent. The hormonal pathways originate at the extracellular domain of the guanylate cyclase; and through a cascade of structural changes in its successive domains activate the C-terminal catalytic domain (CCD). In contrast, the Ca2+ signal operating via its sensor, myristoylated neurocalcin δ both originates and is translated directly at the CCD. Through a detailed sequential deletion and expression analyses, the present study examines the role of the signaling helix domain (SHD) in these two transduction pathways. SHD is a conserved 35-amino acid helical region of the guanylate cyclase, composed of five heptads, each meant to tune and transmit the hormonal signals to the CCD for their translation and generation of cyclic GMP. Its structure is homo-dimeric and the molecular docking analyses point out to the possibility of antiparallel arrangement of the helices. Contrary to the hormonal signaling, SHD has no role in regulation of the Ca2+- modulated pathway. The findings establish and define in molecular terms the presence of two distinct non-overlapping transduction modes of ANF-RGC, and for the first time demonstrate how differently they operate, and, yet generate cyclic GMP utilizing common CCD machinery.